Physicochemical impacts on bacterial communities of selected sites in Putrajaya Lake - Mat Lazim, Nurul Najwa Farihah; Mohamed, Afiqah; Zana Rudin, Zana Ruhaizat; Md Yusoff, Fatimah; Natrah, Ikhsan; Zulkifly, Shahrizim (Universiti Putra Malaysia Press, 2023)
This study determines the associations between the bacterial communities and water physicochemical parameters in Putrajaya Lake and Putrajaya Wetlands Park, Malaysia. Bacterial communities were assessed by metagenomics of the 16S rRNA gene from lake water input, central wetlands, and primary lake area. Water samples (n=18) were collected during two different periods: post-high rainfall events (samples collected in May) and dry periods (July). The data revealed that bacterial communities of the three sites were taxonomically distinct and associated with different environmental parameters. However, no significant differences were found between the wet and dry periods. Alpha diversity analyses revealed the highest index in May 2018 in the constructed wetlands (H’= 5.397) than those from water input or primary lake (p<0.05). Overall, 49 phyla, 147 classes, 284 orders, 471 families, 778 genera and 62 species of bacteria were identified. Verrumicrobia and Firmicutes showed a strong positive correlation with ammonia-nitrogen (r = 0.709). Actinobacteria and Cyanobacteria had a moderate positive correlation with nitrate with r value (r = 0.673) and (r = 0.647), respectively. In this study, the metagenomics of the 16S rRNA gene amplicon by Illumina MiSeq has successfully identified the bacterial community assemblage in Putrajaya Lake and wetlands. Bacterial composition was associated with the availability of physicochemical properties of specific sites. The effectiveness of the engineered wetlands of Putrajaya in bioremediation was demonstrated by the marked decrease in certain nutrient concentrations from lake water input to the primary lake area.